Effectiveness of SDST as a "self-disinfecting" disinfectant - Chua, Lauryn Zhi En (Nanyang Technological University, 2022)
For the past two years, the world experienced a global pandemic caused by the infectious Covid-19 disease, stemming from Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). When the virus reached the shores of Singapore, various measures were put in place to minimize the transmission rates in public settings. One such safety measure included the use of a spray-on disinfecting coating on high-touchpoint surfaces like the lift panels in housing flats. One of the disinfectants was called SDST and was marketed to have self-disinfecting properties. However, no scientific publications were produced to justify its claims. A previous FYP study that tested the effectiveness of the SDST disinfectant against repetitive loadings of bacteria was unable to strongly establish its efficiency due to unreliable findings. The study suggested that the method of testing contributed to the flawed results and therefore advised a different sampling and analysis method to be utilized instead. This study aims to evaluate the effectiveness of SDST as a disinfectant by measuring its disinfection efficiency under different conditions. E. coli bacteria was used as a substitute of the Covid-19 virus due to safety and accessibility reasons. Using stainless-steel plates of the same grade as lift panels, E. coli suspensions at different growth phase and concentrations were attached to the plates and left to dry. Wiping of the plates were performed at varying intervals of every day, every 3 days, and every 7 days. The ATP (adenosine triphosphate) test method was then used to collect and analyze samples. The overall result presented averages of 90% disinfection efficiency for daily wiping conditions and 80% for weekly wiping conditions. Cleaning frequency of once a day was proposed according to the results of this study.